To simplify the expression \(30m + (21m - 53) + (18 - 2m)\) using the Associative Property, we can rearrange and regroup the terms in any way we wish.
Let's break it down step-by-step:
-
Start with the original expression: \[ 30m + (21m - 53) + (18 - 2m) \]
-
Distribute the terms inside the parentheses: \[ = 30m + 21m - 53 + 18 - 2m \]
-
Now, rearranging and combining like terms:
- Combine all \(m\) terms: \[ (30m + 21m - 2m) = 49m \]
- Combine the constant terms: \[ (-53 + 18) = -35 \]
-
Therefore, we obtain: \[ 49m - 35 \]
Now, let's compare this with the provided responses:
- \( (49m - 53) + 16 \) → This is not equivalent.
- \( 51m + (-53 + 18) - 2m \) → This simplifies to \( 51m - 35 - 2m = 49m - 35 \), which is equivalent.
- \( (30m + 21m) + (18 - 2m) \) → This is equivalent as it maintains the grouping.
- \( 53m - 35 \) → This is not equivalent.
Thus, the correct equivalent expression according to the Associative Property is: \[ (30m + 21m) + (18 - 2m) \] This confirms that the associativity allows us to regroup terms, leading to the same final expression of \(49m - 35\).